2022
DOI: 10.3389/fcell.2022.884004
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor: From Homeostasis to Tumor Progression

Abstract: Transcription factor aryl hydrocarbon receptor (AHR) has emerged as one of the main regulators involved both in different homeostatic cell functions and tumor progression. Being a member of the family of basic-helix-loop-helix (bHLH) transcriptional regulators, this intracellular receptor has become a key member in differentiation, pluripotency, chromatin dynamics and cell reprogramming processes, with plenty of new targets identified in the last decade. Besides this role in tissue homeostasis, one enthralling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 170 publications
(223 reference statements)
0
6
0
Order By: Relevance
“…We have shown that Ahr is required to adjust liver regeneration after acute toxic injury 22 and we and others have reported that Ahr serves to reduce hepatocarcinogenesis burden caused by postnatal exposure to diethylnetrosamine in mice 22,41 . Moreover, previous work also suggest that the higher regenerative potential and increased susceptibility to carcinogenesis of Ahr-null mice could be due to their more undifferentiated and pluripotent phenotype in different organs including liver 21,22,30,[42][43][44][45] . In this study, we have investigated potential mechanisms through which Ahr adjusts liver regeneration in response to a massive tissue removal resembling that used in humans.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that Ahr is required to adjust liver regeneration after acute toxic injury 22 and we and others have reported that Ahr serves to reduce hepatocarcinogenesis burden caused by postnatal exposure to diethylnetrosamine in mice 22,41 . Moreover, previous work also suggest that the higher regenerative potential and increased susceptibility to carcinogenesis of Ahr-null mice could be due to their more undifferentiated and pluripotent phenotype in different organs including liver 21,22,30,[42][43][44][45] . In this study, we have investigated potential mechanisms through which Ahr adjusts liver regeneration in response to a massive tissue removal resembling that used in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous ligands of AhR have been identified as agonists of AhR, including synthetic and environmental chemicals [60,61]. Nonetheless, the subsequent discovery of endogenous and plant source ligands led to the recognition that AhR plays a fundamental role in normal cell biology and physiology by ensuring normal development and homeostasis [63][64][65][66][67][68][69][70].…”
Section: Ahr Ligandsmentioning
confidence: 99%
“…Together, all these regulatory elements allow the non-coding region of the genome to maintain the proper balance of gene expression that allows the cell an adaptive response to environmental and homeostatic stimuli [ 16 ]. In the last decade, this type of special regulation, far from the classic transcriptional regulation, has experienced a growing interest, with AHR presenting a pivotal role in the interaction of retrotransposons, chromatin spatial organization and epigenetic modifications [ 17 ].…”
Section: Epigenetics and Chromatin: Ahr-driven Barriersmentioning
confidence: 99%
“…Due to the finding that in the absence of AHR there is differential phosphorylation of several proteins such as fibrillin and fibronectin, it is speculated that the increased phosphorylation of AKT in AHR-/-MLF (mouse lung fibroblast) could be associated with extracellular matrix (ECM) deregulation [ 71 ]. This apparent discordance between the results of different studies suggests that AHR regulation of basal AKT activity may be cell-type specific and/or reflect differences between primary and cancer cells, a well-known feature of AHR [ 17 ].…”
Section: Ahr Signalingmentioning
confidence: 99%